2015
DOI: 10.7717/peerj.1310
|View full text |Cite
|
Sign up to set email alerts
|

Expression of temperature-sensitive ion channel TRPM8 in sperm cells correlates with vertebrate evolution

Abstract: Transient Receptor Potential cation channel, subfamily Melastatin, member 8 (TRPM8) is involved in detection of cold temperature, different noxious compounds and in execution of thermo- as well as chemo-sensitive responses at cellular levels. Here we explored the molecular evolution of TRPM8 by analyzing sequences from various species. We elucidate that several regions of TRPM8 had different levels of selection pressure but the 4th–5th transmembrane regions remain highly conserved. Analysis of synteny suggests… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 87 publications
0
23
1
Order By: Relevance
“…S13 ). Although immunohistochemical evidence has previously suggested that TRPM8 is present in teleost fish (Majhi, et al 2015), we found no evidence of it in available sequences for ray-finned fish, cartilaginous fish, or agnathans ( Fig. 6 and Fig.…”
Section: Resultscontrasting
confidence: 65%
“…S13 ). Although immunohistochemical evidence has previously suggested that TRPM8 is present in teleost fish (Majhi, et al 2015), we found no evidence of it in available sequences for ray-finned fish, cartilaginous fish, or agnathans ( Fig. 6 and Fig.…”
Section: Resultscontrasting
confidence: 65%
“…The Align‐GVGD Web‐based server integrates the biophysical features of amino acids and protein multiple sequence alignments to predict whether missense variants in genes of interest lead to deleterious or neutral effects. This program is an extension of the original Grantham difference to multiple sequence alignments and true simultaneous multiple comparisons [Majhi et al., ]. For Align‐GVGD program, a value of C > 0 was considered deleterious; otherwise a variant was considered to be neutral.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] In agreement with these reports, recent studies have indeed confirmed that different domains and motifs of TRP channels had undergone differential selection pressure throughout vertebrate evolution. 3,5,11 This leads to changes in the sequence of TRP channels, especially in certain key regions affecting its structure -function relationship, which is either beneficial (thus selected) or may become deleterious (thus not selected) during molecular evolution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zebra fish lost TRPM8 during evolution, most likely to increase their reproductive fitness in the cold region of Himalayas where that species have evolved under resource limited conditions. 3 In fact, different species seem to have utilized TRPM8 to respond to different temperatures. This is supported by that fact that African clawed frog Xenopus laevis has a very distinct thermal response property compared to its mammalian and avian counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation